Identification of Atypical El TorV. cholerae O1 Ogawa Hosting SXT Element in Senegal, Africa - Sambe-Ba, Bissoume; Diallo, Mamadou H.; Seck, Abdoulaye; Wane, Abdoul A.; Constantin de Magny, Guillaume; Boye, Cheikh S.-B.; Sow, Ahmad I.; Gassama-Sow, Amy (Frontiers in Microbiology, 2017)
Vibrio cholerae O1 is the causative agent of cholera with classical and El Tor, two well-established biotypes. In last 20 years, hybrid strains of classical and El Tor and variant El Tor which carry classical ctxB have emerged worldwide. In 2004–2005, Senegal experienced major cholera epidemic with a number of cases totalling more than 31719 with approximately 458 fatal outcomes (CFR, 1.44%). In this retrospective study, fifty isolates out of a total of 403 V. cholerae biotype El Tor serovar Ogawa isolates from all areas in Senegal during the 2004–2005 cholera outbreak were randomly selected. Isolates were characterized using phenotypic and genotypic methods. The analysis of antibiotic resistance patterns revealed the predominance of the S-Su-TCY-Tsu phenotype (90% of isolates). The molecular characterization of antibiotic resistance revealed the presence of the SXT element, a self-transmissible chromosomally integrating element in all isolates. Most of V. cholerae isolates had an intact virulence cassette (86%) (ctx, zot, ace genes). All isolates tested gave amplification with primers for classical CT, and 10/50 (20%) of isolates carried classical and El Tor ctxB. The study reveals the presence of atypical V. cholerae O1 El Tor during cholera outbreak in Senegal in 2004–2005.